2011 IEEE/NPSS 24th Symposium on Fusion Engineering 2011
DOI: 10.1109/sofe.2011.6052323
|View full text |Cite
|
Sign up to set email alerts
|

Overview of DIII-D off-axis neutral beam project

Abstract: Abstract-DIII-D has four neutral beam lines (NB). Each of these beam lines has two ion sources, each of which injects up to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The DIII-D tokamak is equipped with eight neutral-beam sources housed in four beamlines. A hydraulic lift can elevate one of the beamlines to steer the beam vertically [11]. When the beamline is elevated, the pair of sources in this beamline aim through a midplane port to a point below the centre in the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The DIII-D tokamak is equipped with eight neutral-beam sources housed in four beamlines. A hydraulic lift can elevate one of the beamlines to steer the beam vertically [11]. When the beamline is elevated, the pair of sources in this beamline aim through a midplane port to a point below the centre in the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Each ion source accelerator grid is focused in the vertical direction at 10 m in front of the grid, while purely diverging in the horizontal plane. This is referred to as normal focus ion source in [23]. Streams of neutral particles launched in a Monte-Carlo algorithm with 0.008 73 rad horizontal divergence and 0.0227 rad vertical divergence produces a far-field diverging beam that agrees with imaging measurements [29].…”
Section: Neutral Beam Geometry In Nubeammentioning
confidence: 92%
“…In 2010-2011 the 150 • beamline was upgraded to enable tiltable off-axis injection with a maximum beamline angle of 16.3 • downward with respect to the vessel midplane, in the nominal co-current direction [23]. The initial assessment of the power delivered by the tilted beam indicated that less power was produced than expected [24], and subsequent study revealed additional losses and heating of internal beamline components [25,26].…”
Section: Neutral Beam Geometry and Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, all eight sources injected into the tokamak at the midplane of the vacuum vessel. Prior to the 2011 experimental campaign, a massive hydraulic lift was installed beneath one of the beamlines to allow vertical steering [6]. When the beamline is elevated, the pair of sources in this beamline inject neutrals through the midplane port and below the midplane in the plasma.…”
Section: Introductionmentioning
confidence: 99%